Self Powered Sensor Based Environmental Bridge Condition Monitoring System Using Gsm (International Journal of Engineering and Computer Science, 2017)
Basically, in this project we are going to monitor the parameters of the bridge which will help us to maintain the bridge and detect the faults in it. The real-time safety evaluation of bridges includes the following components: (1) real-time analysis of pressure (2) real-time analysis of temperature (3) real-time analysis of tilt (4) real-time analysis of weight (5) real-time analysis of flood (6) real- time boat detection. The sensors will detect the condition of the changing parameter of the bridge. The sensors installed on main cables, hangers, decks, towers, etc detect the strain, acceleration, temperature, wind and water level. The advancement in wireless technology has provided a motive to develop the wireless network based bridge health monitoring system. Sensor technologies have made the monitoring process more accurate and fast. GSM technology is suggested to send the data to the remote location in which the maintenance office is located. This project is useful for monitoring the faults and errors in the bridge and will help to prevent the loss of human life. It will also save the hazards which will create distractions in human life.